Agri-Food Policy Impact on Farm-Household Food Security in SSA: Country cases - Louhichi, Kamel; Gomez y Paloma, Sergio; Tillie, Pascal; Riesgo, Laura (2016)
Going the Last Mile: Accelerating Progress in Food Security and Nutrition workshop (June 14, 2016)